Socializing Saving Through Piggy Banks: Community Service Program at SDN 1 Halimpu - Ramadhan, Gilang; Rahmawati, Elin Maulida; Nilasari, Yekti; Salsabila, Nasywa Mocherine; Nurlatifah, Hana; Seftiani, Shela (Jurnal Pengabdian Kepada Masyarakat Untukmu Nusantara, 2026)
Saving is a simple but essential habit to foster frugality, discipline, and responsibility from an early age. In reality, many elementary school students are not yet accustomed to setting aside their pocket money for savings. This encouraged the Community Service Program (KKN) students of Universitas Nahdlatul Ulama Cirebon to implement an activity entitled “Teaching Frugality through Piggy Banks” at SDN 1 Halimpu, Beber District, Cirebon Regency. The target participants were fourth-grade students. The implementation methods included delivering material on the importance of saving, distributing piggy banks, conducting piggy bank decorating sessions to foster creativity, direct saving practices, and providing rewards to increase motivation. The results revealed that students enthusiastically participated in all activities, understood the importance of saving, and began to develop the habit of setting aside part of their pocket money. This program demonstrates that basic financial literacy can be introduced from an early age through simple, creative, and enjoyable approaches. Thus, the activity not only provided short-term benefits in terms of students’ understanding but also is expected to foster sustainable positive habits.